DEMODULATOR THAT CONVERTS ENCODER STEREO SIGNAL INTO L AND R AUDIO SIGNAL - Ibrahim Ashari; Faisol Ahmad (Merdeka Malang University, 2020)
As technology develops in today’s age, there are many radio equipment easily found in the market. Certainly, there is a stereo decoder module inside a FM radio receiver which operates to return radio signal that previously was modulated and broken apart into stereo audio signal (L+R) and (L-R). There are many stereo decoders already presented inside FM radio receivers. Based on this premise, there is a problem that can be studied, which is how to design a decoder stereo in a stereo FM radio receiver that functions as the demodulation in stereo FM radio and operates to release L+R audio signal to a receiver radio. Therefore, it needs a signal demodulatorof encoder stereo that converts L and R audio signal. Based on the testing result, it showed that sideband frequency from the result of DSB-SC demodulator process, which was produced through R and L channels, still had frequency value differences with average percentage of 1.416% out of the expected frequency value. This was due to the frequency oscillator from the generator function.